A preliminary report about the detection of ventricular repolarisation in patients with non-alcoholic fatty liver disease. Issue 4 (August 2020) - Al-Nimer, Marwan S.; Esmail, Vian A.; Hamid, Dler S.; Mohammad, Mohammad O.
الملخص: أهداف البحث: مرض تشحم الكبد اللاكحولي هو مرض متعدد الأسباب، ويمكن أن يؤثر في الجهاز القلبي الوعائي. ولأجل تقييم تأثيراته في الجهاز القلبي الوعائي، تم التقصي عن إيصال النبضة القلبية وإعادة استقطاب البطين الأيسر في تخطيط القلب الكهربائي. طرق البحث: أجريت هذه الدراسة من آب ٢٠١٨ مرورا آب ٢٠١٩ في قسم الأدوية السريرية / كلية الطب، في جامعة السليمانية. تم إخضاع ٢٣ مريضا يتصفون بعوامل الخطورة لمرض تشحم الكبد اللاكحولي (المجموعة ١)، و٧٤ مريضا يشخص لأول مرة بمرض تشحم الكبد اللاكحولي (المجموعة ٢) في مستشفى شار التعليمي في مدينة السليمانية بالعراق. تم تحليل نتائج القياسات البشرية، ومستويات الشحوم والسكر الصائم، وتخطيط القلب الكهربائي في هذه الدراسة. النتائج: أظهرت مخططات القلب الكهربائي زيادة ذات دلالة نوعية في طول فترة PR وقصر ذا دلالة نوعية في فترة QTcB ، وJTc مع زيادة نسبة Tp-e/QTcB عند مرضى المجموعة ٢ مقارنة بالمجموعة ١ ولم يلاحظ علاقة هذه التغيرات مع مرض السكري كعامل خطورة. كما تم ملاحظة علاقة طردية بين مستويات أنزيمات الكبد وطول الفترة TQ. الاستنتاجات: وجود تغيرات نوعية في إعادة استقطاب البطين الأيسر يدلناعلى أن مرضى تشحم الكبد اللاكحولي حديثي التشخيص يعانون من إجهاد قلبي غير ظاهر سريريا، وهم أكثر تعرضا لخطورة عدم انتظام ضربات القلب. Abstract: Objectives: Non-alcoholic fatty liver disease (NAFLD) is a multisystem disease which can affect the cardiovascular system as well. We conducted this study to determine the cardiac effects of NAFLD such as conduction of impulse and ventricular repolarisation on electrocardiography (ECG). Methods: In this study, we recruited patients with risk factors for NAFLD (group I; n = 23) and NAFLD patients (group II; n = 74) from Shar Hospital in Sulaimani City, Iraq. We analysed anthropometric measurements, serum fasting lipid profile, glucose levels, liver enzymes, and ECG recordings. Results: ECG recordings showed significantly longer PR intervals, significantly shorter QTcB and JTc intervals, and a higher Tp-e/QTcB ratio in group II patients than in group I patients. These abnormalities were not associated with risk factors for diabetes. The TQ duration was significantly correlated with serum alanine aminotransferase (r = 0.411, p  < 0.001) and aspartate aminotransferase (r = 0.272, p  = 0.019) levels. Conclusion: In our study, the presence of significant abnormalities in ventricular repolarisation suggests that patients with newly diagnosed NAFLD have subclinical cardiac stress and a higher risk of ventricular arrhythmias. Highlights: Non-alcoholic fatty liver disease patients are at risk of developing ventricular repolarization. Abnormal electrocardiograph changes are related to the serum levels of liver enzymes. People at risk of developing non-alcoholic liver disease are also have abnormal ventricular repolarization indices.